The Effect of E-WOM on Repurchase Intention Mediated by Brand Image, Brand Trust, and Brand Attitude Among Smartphone Consumers in West Sumatra - Nadila Aprilyra; Yasri Yasri (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of e-WOM on repurchase intention, mediated by brand image, brand trust, and brand attitude, among smartphone users in West Sumatra. The population of this study consists of smartphone consumers residing in West Sumatra. Since West Sumatra comprises 12 regencies and 7 cities, 3 cities and 3 regencies were selected. The sample size for this study was 140 respondents. Data were collected via an online questionnaire distributed through Google Forms and analyzed using SmartPLS4. The findings of this study indicate that e-WOM has a significant effect on repurchase intention; e-WOM has a significant effect on brand image; e-WOM has a significant effect on brand trust; e-WOM has a significant effect on brand attitude, brand image does not have a significant effect on repurchase intention, brand trust has a significant effect on repurchase intention, brand attitude has a significant effect on repurchase intention, e-WOM does not mediate the effect of brand image on repurchase intention, e-WOM mediates the effect of brand trust on repurchase intention, and e-WOM mediates the effect of brand attitude on repurchase intention.